Datalog+/-: A Family of Languages for Ontology Querying. - Calì, A; Gottlob, G; Lukasiewicz, T; Pieris, A (Springer, 2010)
In ontology-based data access, an extensional database is enhanced by an ontology that generates new intensional knowledge which has to be considered when answering queries. In this setting, tractable data complexity (i.e., complexity w.r.t. the data only) of query answering is crucial, given the need to deal with large data sets. This paper summarizes results on a recently introduced family of Datalog-based languages, called Datalog+/-, which is a new framework for tractable ontology querying. Plain Datalog is extended by allowing existential quantifiers, the equality predicate, and the truth constant false to appear in rule heads. At the same time, the resulting language is syntactically restricted, so as to achieve decidability and even tractability. © 2011 Springer-Verlag.